1962
DOI: 10.1084/jem.115.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Transferrins of Adult Serum, Cord Serum, and Cerebrospinal Fluid

Abstract: Recent population studies by starch gel electrophoresis have revealed an elaborate genetically determined polymorphism of human and primate transferrin, the iron-binding protein in serum. At the present time twelve different molecular species of human transferrin have been identified (1). Transferrins whose electrophoretic mobilities are faster than the common type C are labeled B, and slower moving variants are labeled D. With the exception of transferrin C, which is found in high frequency in all populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

1966
1966
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(34 citation statements)
references
References 32 publications
2
31
0
1
Order By: Relevance
“…The changes in Tf microheterogeneity patterns in fetal blood may result from a deficiency in the multiglycosyltransferase. Parker and Bearn [10] described that the faint, slower moving Tf bands in the cord serum of premature infants clearly identified in starch gel electrophoresis disappeared from the serum of the infants approximately 12 weeks after birth. Van Pelt et al [19] also demonstrated that carbohydrate-deficient Tf values (CDT, ^2-sialo-Tfs) in the cord serum of infants decrease rapidly after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in Tf microheterogeneity patterns in fetal blood may result from a deficiency in the multiglycosyltransferase. Parker and Bearn [10] described that the faint, slower moving Tf bands in the cord serum of premature infants clearly identified in starch gel electrophoresis disappeared from the serum of the infants approximately 12 weeks after birth. Van Pelt et al [19] also demonstrated that carbohydrate-deficient Tf values (CDT, ^2-sialo-Tfs) in the cord serum of infants decrease rapidly after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al [10,11] first demonstrated by vertical starch gel electrophoresis that different patterns of multiple faint Tf bands, which were related to the number of sialic acids on a Tf molecule, were observed between umbilical cord serum and adult serum. Verrijt et al [12] indicated a shift in the pattern of fetal Tf heterogeneity towards hyposialylated Tf fractions (^2-sialo-Tf) relative to maternal serum Tf by isoelectric focusing, but without determination of the percentage distribution of the Tf subfractions.…”
Section: Introductionmentioning
confidence: 99%
“…Several workers report th at differences in sialic acid content do not account for complex transferrin phenotypes of mammals (Gordon and Louis [1963]; Parker and Bearn [1962]; Blumberg and Warren [1961]). These reports are not supported by our work.…”
Section: Discussionmentioning
confidence: 99%
“…A number oftransferrin variants have been described which show characteristic peptide maps suggestive of differences in primary structure (5,14). At Moqbel, and J. MacKay, unpublished observations).…”
Section: Al|eanti-gpbp1mentioning
confidence: 96%